“Just for the Sake of Comparison”. Some Thoughts on Batchelor’s Linguistic Skills and the Validity of His Ainu Language Data - de la Fuente, José Andrés Alonso (Silva Iaponicarum, 2024)
When describing John Batchelor’s Ainu language data, it is a trope in the field to dismiss them out of hand due to Batchelor’s lack of linguistic training. Some specialists, however, consider such a statement an exaggeration. Whereas it is undeniable that the Ainu texts composed by Batchelor for indoctrination purposes are less than satisfactory, excerpts of oral tradition recorded by him (or under his supervision) are as good as those which have been gathered in more recent times in full agreement with contemporary linguistic conventions. In order to show that this is indeed the case, the author compares the text of an oral composition which has come down to us in two versions: one by Batchelor, the other by Bronisław Piłsudski. It turns out that both versions are virtually the same. Since Piłsudski’s linguistic skills have been universally praised (and rightly so), it naturally follows that there exist instances like the present one when Batchelor’s Ainu language data must be approached with more respect than it is usually done.